Working Hard in the Wrong Place: A Mismatch-Based Explanation to the UK Productivity Puzzle - Christina Patterson; Aysegül Sahin; Giorgio Topa; Giovanni L. Violante (Institute for the Study of Labor (IZA), 2016)
The UK experienced an unusually prolonged stagnation in labor productivity in the aftermath of the Great Recession. This paper analyzes the role of sectoral labor misallocation in accounting for this "productivity puzzle." If jobseekers disproportionately search for jobs in sectors where productivity is relatively low, hires are concentrated in the wrong sectors, and the post-recession recovery in aggregate productivity can be slow. Our calculations suggest that, quantified at the level of three-digit occupations, this mechanism can explain up to two thirds of the deviations from trend-growth in UK labor productivity since 2007.
Keywords: E24; E32; J24; 330; misallocation; productivity